Method Comparison of the ImmuView L. pneumophila and L. longbeachae Urinary Antigen Test with the BinaxNOW Legionella Urinary Antigen Card for Detection of Legionella pneumophila Serogroup 1 Antigen in Urine - Badoux, Paul (J Clin Microbiol, 2020)
We compared the clinical performance of the ImmuView L. pneumophila and L. longbeachae urinary antigen test (SSI Diagnostica A/S, Hillerød, Denmark) to that of the BinaxNOW Legionella urinary antigen card (Binax; Abbott, Lake Buff, IL) using urine specimens from patients suspected of having pneumonia. In total, 100 frozen urine samples (derived from 50 Legionella cases and 50 noncases) were analyzed with both tests, as were 200 nonfrozen prospectively collected samples. For urine samples from five Legionella cases and two non-Legionella cases, analytical sensitivity (limit of detection) and repeatability were examined. The urine samples from the five Legionella cases were diluted with urine samples that tested Legionella urinary antigen negative with both tests. The analyses of the 100 frozen samples resulted in a sensitivity and specificity of both ImmuView and the BinaxNOW of 96.0% (48/50) and 100% (50/50), respectively. Of the 200 nonfrozen samples, there were three samples that showed a positive result for L. pneumophila by both tests. The analyses of reproducibility showed that for the 34 (diluted) samples that were tested at two consecutive times, 33 samples showed a consistent result for both the ImmuView and the BinaxNOW tests (Cohen’s kappa values of 0.916 and 0.928). In addition, the ImmuView test may have detected two L. longbeachae-positive urine samples, although other diagnostic tests could not confirm this. Both ImmuView and BinaxNOW showed high sensitivity and specificity for the detection of L. pneumophila serogroup 1 antigen in urine samples from clinical patients with a suspected lower respiratory tract infection.